Investigation of the Atypical Glass Transition and Recrystallization Behavior of Amorphous Prazosin Salts - Arvind K. Bansal; Dharmesh Popat; Lokesh Kumar (MDPI AG, 2011)
This manuscript studied the effect of counterion on the glass transition and recrystallization behavior of amorphous salts of prazosin. Three amorphous salts of prazosin, namely, prazosin hydrochloride, prazosin mesylate and prazosin tosylate were prepared by spray drying, and characterized by optical-polarized microscopy, differential scanning calorimetry and powder X-ray diffraction. Modulated differential scanning calorimetry was used to determine the glass transition and recrystallization temperature of amorphous salts. Glass transition of amorphous salts followed the order: prazosin mesylate > prazosin tosylate ~ prazosin hydrochloride. Amorphous prazosin mesylate and prazosin tosylate showed glass transition, followed by recrystallization. In contrast, amorphous prazosin hydrochloride showed glass transition and recrystallization simultaneously. Density Functional Theory, however, suggested the expected order of glass transition as prazosin hydrochloride > prazosin mesylate > prazosin tosylate. The counterintuitive observation of amorphous prazosin hydrochloride having lower glass transition was explained in terms of its lower activation energy (206.1 kJ/mol) for molecular mobility at Tg, compared to that for amorphous prazosin mesylate (448.5 kJ/mol) and prazosin tosylate (490.7 kJ/mol), and was further correlated to a difference in hydrogen bonding strength of the amorphous and the corresponding recrystallized salts. This study has implications in selection of an optimal amorphous salt form for pharmaceutical development.